PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KUALITAS PELAYANAN PUBLIK MELALUI MOTIVASI KERJA DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKANBARU - , Kurniawaty Fitri, Fitria Febriani , Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aimed to examine the influence of Leadership and Work Discipline on the Quality of Public Services through Work Motivation in the Department of Population and Civil Registration in the city of Pekanbaru. This study uses a quantitative approach. The sample in this study was 100 employees at the Department of Population and Civil Registration in the city of Pekanbaru. Sampling using the Saturated sampling technique method. The research instrument used a questionnaire and was analyzed using path analysis using SPSS. The results of the study show that 1) There is a positive and significant influence between leadership and the quality of public service, 2) There is a positive and significant influence between work discipline and the quality of public service, 3) There is a positive and significant influence between work motivation and service quality public, 4) There is a positive and significant influence between leadership and the quality of public services through work motivation, 5) There is a positive and significant influence between work discipline and the quality of public services through work motivation. Keywords :  Leadership, Work Discipline, Work Motivation and Public Service Quality